MASS TRANSFER MODEL FOR CONCENTRATING SIAM JUICE BY LOW PRESSURE REVERSE OSMOSIS - Erliza Noor, Adetiya Rachman, Setyajit (Department of Agroindustrial Technology, Bogor Agricultural University, 2010)
ABSTRACT This research studied mass transfer model for concentrating siam juice by low pressure reverse osmosis (LPRO). A spiral wound module equipped by a polyamide membrane was operated at various transmembrane pressures and crossflow velocities. The permeate flux was predicted by using a modification of Solution-Diffusion (SD) with thin film model and adsorption resistance model. Modified solution diffusion model with adsorption resistance predicted well the flux for LPRO (< 8 bars) compared to modified solution diffusion and thin film model. Concentrating of juice by LPRO was more influenced by adsorption rather than by deposition of solute on the membrane surface. Keywords: low pressure reverse osmosis, concentration of siam juice, solution diffusion model, adsorption